"A Clear Account of the Codex Simonideios:" Ideological Infrastructures of Biblical Vulnerability in the Nineteenth Century. - Jacobs, Andrew S. (Philological Encounters, 2026)
Soon after Constantin Tischendorf (1815–74) publicized his "discovery" of the Codex Sinaiticus, notorious manuscript broker (and forger) Konstantinos Simonides stunned elite literary circles by announcing that Simonides himself had produced this biblical codex in his youth as a gift for the Russian tsar. Simonides claimed that his "Codex Simonideios" was illicitly being passed off as an ancient biblical codex after being mutilated and disfigured. I argue that this brief but explosive debate about manuscripts, forgeries, and "find" narratives produces a biblical text liable to revision and emendation, due to new discoveries or new methods, and so vulnerable to mischievous actors manipulating the possibilities of new discoveries and methods. The iterative process of attack and defense on display in this codicological debate has remained, in various guises, from collegial disagreement to scorched earth campaigns, an ideological component of critical biblical studies.